2019
DOI: 10.1103/physrevlett.122.041801
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Hidden Photons Produced in Nuclear Reactors

Abstract: New light vector particles -hidden photons -are present in many extensions of the Standard Model of particle physics. They can be produced in nuclear reactors and registered by neutrino detectors. We obtain new limits on the models with the hidden photons from an analysis of published results of the TEXONO neutrino experiment. Accounting for oscillations between the visible and hidden photons, we find that the neutrino experiments are generally insensitive to the hidden photons lighter than ∼ 0.1 eV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…For detailed discussion of various limits, see e.g. [6,7,29,30]. One may argue that the bounds from stellar cooling are considerably more stringent than those from any expected direct searches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For detailed discussion of various limits, see e.g. [6,7,29,30]. One may argue that the bounds from stellar cooling are considerably more stringent than those from any expected direct searches.…”
Section: Resultsmentioning
confidence: 99%
“…[5]). In particular, applying oscillations to describe the hidden photon behavior in a nuclear reactor it has been recently found [6] that, generically, there are no chances to produce too light hidden photon there. The reason is that the visible photon either gets absorbed or scatters in media before oscillating into the hidden photon.…”
Section: Introductionmentioning
confidence: 99%
“…Second, photon can be absorbed in matter, and in water the absorption length for E γ ∼ 1 − 10 MeV is about 1/Γ 10 cm , that is smaller than the reactor size. At the distance exceeding absorption length, L 1/Γ, the probability to observe the hidden photon approaches [3,7]…”
Section: Vector Portal To the Hidden Worldmentioning
confidence: 99%
“…Within the oscillation approach one can analyze the results of neutrino reactor experiments and place the limit on model parameters given the full consistency of these results with neutrino oscillations. The investigation [3] revealed that mostly sensitive experiment is TEX-ONO [8], which allows one to constrain the model parameter space as depicted in Fig. 4.…”
Section: Vector Portal To the Hidden Worldmentioning
confidence: 99%
See 1 more Smart Citation